2023
DOI: 10.3390/ijms24031926
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Required to Sustain Increased Intestinal Cell Proliferation during Phenotypic Plasticity Changes in Honey Bee (Apis mellifera)

Abstract: Tissue phenotypic plasticity facilitates rapid adaptation of organisms to biotic and/or abiotic pressure. The reproductive capacity of honey bee workers (Apis mellifera) is plastic and responsive to pheromones produced by broods and the queen. Egg laying workers (ELWs), which could reactivate their ovaries and lay haploid eggs upon queen lost, have been commonly discussed from many aspects. However, it remains unclear whether midgut homeostasis in ELWs is affected during plastic changes. Here, we found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Yang et al [ 6 ] demonstrated that autophagy is required for ileal stem cell maintenance and mammalian survival. In addition, recent studies have shown that autophagy is required to maintain increased enterocyte proliferation in honeybees[ 7 ].…”
Section: Autophagy and Gi Cellsmentioning
confidence: 99%
“…Yang et al [ 6 ] demonstrated that autophagy is required for ileal stem cell maintenance and mammalian survival. In addition, recent studies have shown that autophagy is required to maintain increased enterocyte proliferation in honeybees[ 7 ].…”
Section: Autophagy and Gi Cellsmentioning
confidence: 99%